Optimized design and experiment of a fully automated potted cotton seedling transplanting mechanism - Xue, Xianglei; Li, Lianhao; Xu, Chunlin; Li, Enquan; Wang, Yujie (International Journal of Agricultural and Biological Engineering, 2020)
In order to improve the accuracy and stability of transplanting machine seedling picking, a seedling pick-up mechanism was designed, which was controlled by a controller and driven by brushless DC servo motor. At the same time, the parameters of the seedling manipulator were optimized: the mathematical model for the seedling pick-up mechanism was established. According to the predetermined trajectory requirements, the objective function and constraint conditions were proposed, and then the optimal size was obtained by a multi-objective genetic algorithm. At last, Automatic Dynamic Analysis of Mechanical Systems (ADAMS) software was used to simulate and analyze the kinematics and trajectory of the seedling pick-up mechanism, and the mechanism was tested to verify the effectiveness of the mechanism prototype. The experiments showed that the success rate of seedling picking was 94.32%, the rate of acceptably planted seedlings was 96.67%, and the rate of excellently planted seedlings was 63.48%. Keywords: cotton seedling, transplanting machine, kinematic model, optimized design, test, full automation DOI: 10.25165/j.ijabe.20201304.5317 Citation: Xue X L, Li L H, Xu C L, Li E Q, Wang Y J. Optimized design and experiment of a fully automated potted cotton seedling transplanting mechanism. Int J Agric & Biol Eng, 2020; 13(4): 111–117.